Thermophysical, rheological and electrical properties of mono and hybrid TiB2/B4C nanofluids based on a propylene glycol:water mixture - Vallejo, Javier P.; Zyla, Gawel; Ansia, Lucas; Fal, Jacek; Traciak, Julian; Lugo, Luis (Powder Technology 395 (2022) 391-399, 2021)
Hybrid nanofluids aim to further improve the characteristics of mono nanofluids. However, experimental studies that jointly explore the physical properties of hybrids and the corresponding mono nanofluids are missing. In this work, mono B4C and TiB2 and hybrid TiB2:B4C nanoadditives are used for the first time to design nanofluids based on propylene glycol:water 20:80 wt%. The density, isobaric heat capacity, and thermal conductivity of the nanofluids are determined by the oscillating U-tube, differential scanning calorimetry, and transient hot wire methods, respectively. The rheological behaviour is investigated through rotational rheometry. Additionally, surface tension and electrical conductivity are investigated. The B4C mono nanofluid shows the highest improvements of thermal conductivity (6.0%) and electrical conductivity (70 times higher), but also the highest viscosity increases (51–54%). The hybrid nanofluid presents intermediate values between those of the mono nanofluids for all the properties except dynamic viscosity. Interactions between spherical and sheet-like nanoparticles explain this behaviour.